2023
DOI: 10.1007/s12155-023-10689-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inoculum to Substrate Ratio and Substrates Mixing Ratio on Biogas Production from the Anaerobic Co-digestion of Phragmites australis and Food Waste

Ahmed R. Al-Iraqi,
Bhushan P. Gandhi,
Andrew M. Folkard
et al.

Abstract: This study focused on determining the effect of the inoculum to substrate ratio (ISR) on biogas production efficiency from the anaerobic co-digestion of two substrates: synthetic food waste and common reeds (Phragmites australis) that were ground and pre-treated using sodium hydroxide at a concentration of 2% to increase access to their cellulose. It also studied the role of different mixing ratios of the two substrates in improving the stability of the digestion process and increasing biogas production. A ser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Theoretically, it should not affect the value of the methane/biogas yield but only the kinetics of the process, including the length of the lag phase (it shortens as the I/S value increases) [36][37][38]. Numerous literature reports, however, demonstrate the significance of the I/S ratio in preventing the process inhibition caused by the accumulation of inhibitors like VFAs, while also impacting the efficacy of the anaerobic digestion process [39]. Each substrate has an optimal characteristic value of the I/S ratio, and its value is a specific compromise between the endogenous production of inoculum biogas, the acceptable lag phase length, and the buffer capacity.…”
Section: Determination Of the Inoculum-to-substrate Ratio (Isr I/s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, it should not affect the value of the methane/biogas yield but only the kinetics of the process, including the length of the lag phase (it shortens as the I/S value increases) [36][37][38]. Numerous literature reports, however, demonstrate the significance of the I/S ratio in preventing the process inhibition caused by the accumulation of inhibitors like VFAs, while also impacting the efficacy of the anaerobic digestion process [39]. Each substrate has an optimal characteristic value of the I/S ratio, and its value is a specific compromise between the endogenous production of inoculum biogas, the acceptable lag phase length, and the buffer capacity.…”
Section: Determination Of the Inoculum-to-substrate Ratio (Isr I/s)mentioning
confidence: 99%
“…Above the indicated value, they observed a decrease in biogas production, which they associated with the imbalance of nutrients in the feedstock (fruit and vegetable waste). In turn, Al-Iraqi et al [39], for a feedstock composed of simulated food waste and common reeds, recommend an I/S ratio of 1. Other studies have shown that, for easily biodegradable substrates like household waste, I/S ratios ranging from 5 to 15 are suitable for batch assays without volatile fatty acid accumulation [41].…”
Section: Determination Of the Inoculum-to-substrate Ratio (Isr I/s)mentioning
confidence: 99%